Active Imagination and Personal Shadows: A Shortcut to the Unconscious and its Integration (Interapia – Journal of Clinic, Culture and Mental Sciences, 2025)
Abstract The study introduces the LS (Light and Shadow) Protocol, a structured adaptation of Jung’s active imagination technique aimed at integrating shadow aspects of the psyche. Grounded in Carl Jung’s shadow theory, it outlines theoretical foundations, methodology, and findings from a pilot study with two participants across thirteen sessions. Qualitative reports indicate behavioral and emotional transformation and enhanced psychic balance. While preliminary results are promising, the author highlights methodological limitations and calls for further empirical validation. The study contributes to analytical psychology by systematizing an accessible method for shadow integration and individuation.
Keywords: Shadow; Unconscious; Active imagination; Integration; LS protocol